2017
DOI: 10.1109/tac.2016.2580662
|View full text |Cite
|
Sign up to set email alerts
|

Design of Robust Controller for a Class of Uncertain Discrete-Time Systems Subject to Actuator Saturation

Abstract: This paper studies the robust output tracking controller design for a class of uncertain discrete-time systems subject to actuator saturation. To achieve this capability, a new controller is proposed by robustifying the Discrete-time Composite Nonlinear Feedback (DCNF) control law. Since, the proposed controller may be saturated; a precise analysis is done to show its robust performance in spite of presence of actuator saturation and time-varying external disturbances. Additionally, a theorem is given and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In contrast to normal systems, the solution P of GLE (13) for a positive definite matrix Q is not unique. However, it has been proved in the work of Ishihara and Terra 29 that E T PE ≥ 0 is unique for any solution P of GLE (13). In addition, the partition of P corresponding to the dynamic part of the singular system (due to the standard decomposition of singular systems mentioned in the work of Duan 26 ) is a unique positive definite matrix and satisfies the normal Lyapunov equation.…”
Section: Remark 2 Figure 1 Depicts a Simple Two-dimensional Scheme Omentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to normal systems, the solution P of GLE (13) for a positive definite matrix Q is not unique. However, it has been proved in the work of Ishihara and Terra 29 that E T PE ≥ 0 is unique for any solution P of GLE (13). In addition, the partition of P corresponding to the dynamic part of the singular system (due to the standard decomposition of singular systems mentioned in the work of Duan 26 ) is a unique positive definite matrix and satisfies the normal Lyapunov equation.…”
Section: Remark 2 Figure 1 Depicts a Simple Two-dimensional Scheme Omentioning
confidence: 99%
“…4 Practical advantages of the CNF controller compared to other methods such as antiwindup controller 5,6 and proximate time optimal servomechanism, 7 which also considered the actuator saturation constraint, motivated the researchers to use the CNF control method, increasingly. Later, numerous studies were performed on CNF control such as investigating the CNF control method for a class of nonlinear systems, 8,9 robustifying CNF control laws in continuous [10][11][12] and discrete-time systems, 13 developing CNF controller for nonstep tracking problems, [14][15][16] transient performance improvement of nonlinear systems, 17 master-slave synchronization, 18 and path following. 19,20 Some other recent studies in this field can be observed in other works.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a multirate disturbance compensator with fast sampling is designed to compensate the inter-sample ripples. Inspired by [22], [23], a discrete composite controller is designed in the feedback loop so as to improve the transient positioning performance and stabilize the system. Furthermore, the estimation convergence and the stability are analyzed by means of Lyapunov methods.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with saturation nonlinearity, different methods have been proposed, including the convex combination method (Hu et al, 2002), dead-zone function method (Tong and Li, 2013) and anti-windup compensation method (Gayadeen and Duncan, 2016; Li et al, 2016a; Li and Lin, 2014). For local stability, scholars are devoted to calculating the domain of attraction for both continuous-time systems (Mohammadpour and Binazadeh, 2018; Tarbouriech et al, 2011; Zuo et al, 2010) and discrete-time systems (Binazadeh and Bahmani, 2017; Gayadeen and Duncan, 2016).…”
Section: Introductionmentioning
confidence: 99%